Serf, Seigneur, and Sovereign : Agrarian Reform in Eighteenth-Century Bohemia. - Wright, William E. (University of Minnesota Press, 1966)
This is a detailed history of the agrarian reforms which took place in Bohemia during the reigns of the Habsburg rulers Maria Theresa, 1740-1780, and Joseph II, 1780-1790. The enactment of the land reforms had far-reaching social, economic, and political.